Criminal Responsibility for Perpetrators of Destruction of Rupiah Banknotes in the Perspective of Law Number 7 of 2011 concerning Currency - Van Lodewijk Purba; Muhammad Fadly Nasution; Desy Kartika C. Sitepu; Audi Katalino (KOLABORASI: Journal of Multidisciplinary, 2025)
As an independent and sovereign country, the Unitary State of the Republic of Indonesia has a symbol of sovereignty that must be respected by all its people, one of which is the Rupiah currency, which is often damaged, especially small denominations and is often carried out by minors, thus giving rise to problems that require a more in-depth study of the legal regulations related to the damage to banknotes, forms of damage according to Law Number 7 of 2011 concerning Currency, and criminal liability for the perpetrators of these acts, which in this study were analyzed using library research methods through various sources, both printed and electronic, so that it was concluded that the regulations regarding the damage to banknotes have been regulated in laws and regulations that provide the threat of sanctions in the form of imprisonment or fines in accordance with applicable laws, where the form of damage to banknotes according to Law Number 7 of 2011 includes changes in the original physical shape or size such as burning, making holes, tearing, cutting, destroying, and changing the value of the Rupiah with the intention of degrading the country's currency, and that criminal liability for perpetrators of damage to Rupiah banknotes still refers to the provisions of the applicable laws in The Unitary State of the Republic of Indonesia